2009
DOI: 10.2495/op090211
|View full text |Cite
|
Sign up to set email alerts
|

Silo foundation optimization through reinforcement concrete shell structure

Abstract: The objective of the present work is to perform a technical and economic analysis of the adoption of shell as a structural solution for the foundation of industrial vertical silo. Initially projected in a rigid and flat slab, the foundations of a vertical silo were optimized by numerical computational modeling through a parallel Finite Element Method code, adopting shell in the form of reversed cone. It will be shown that a significant reduction of structural concrete of steel was obtained with the optimizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Martins et al [24] evaluated the feasibility and costeffectiveness of using shell as the structural solution for the base of industrial vertical silos. In order to optimize the base of a vertical silo, which was originally projected as a solid and flat slab, engineers used numerical computer modeling in the form of a parallel Finite Element Method code to create a shell in the shape of a reversed cone.…”
Section: Numerical Overview Researchesmentioning
confidence: 99%
“…Martins et al [24] evaluated the feasibility and costeffectiveness of using shell as the structural solution for the base of industrial vertical silos. In order to optimize the base of a vertical silo, which was originally projected as a solid and flat slab, engineers used numerical computer modeling in the form of a parallel Finite Element Method code to create a shell in the shape of a reversed cone.…”
Section: Numerical Overview Researchesmentioning
confidence: 99%
“…Martins et al [8] performed a technical and economic analysis of the adoption of shell as a solution for the foundation of an industrial vertical silo, where a rigid and flat slab foundation was initially designed. The results showed that steel consumption was reduced by 23 % of the initial value, while structural concrete consumption was reduced to about 60 %.…”
Section: Introductionmentioning
confidence: 99%
“…Ensuring of reliability and safety of operation of metallic silos with the goal of decreasing of foundation settlements is topical both for new building and for objects already brought into operation [1][2][3][4][5] . Taking into account requirements of effective land legislation to efficient land management, new building is planned on plots unsuitable for agriculture.…”
Section: Introductionmentioning
confidence: 99%